Tragedi Kanjuruhan dalam Perspektif Sosiologi Olahraga : Tinjauan Literatur dalam Laga Arema FC vs Persebaya - Mohammad Noval Baghaskara; Aulya Safiyna Nuuril Anwari; Himawan Wismanadi (Atletik Karya: Jurnal Pendidikan dan Olahraga Aktual, 2025)
The Kanjuruhan tragedy on October 1, 2022, marks one of the deadliest disasters in Indonesian sports history, resulting in the deaths of over a hundred spectators during a post-match riot. This study explores the tragedy through the lens of sports sociology by examining how crowd behavior, institutional failures, and the use of excessive force reflect deeper socio-political dynamics. Using a library research method, this paper analyzes academic literature, official reports, and sociological theories—particularly those of Gramsci, Bourdieu, and Foucault—to understand the normalization of violence, the exercise of hegemonic power through sport, and the systemic weaknesses in match organization. The study finds that the convergence of commercial interests, inadequate crowd management, and institutionalized violence created the conditions for this disaster. The findings call for structural reforms in sports governance and advocate for a sociologically informed approach to fan education, crowd control, and ethical media representation.